A Case Report of Isolated Cuboid Nutcracker Fracture - Takaaki Ohmori; Shinichi Katsuo; Chiaki Sunayama; Katsunori Mizuno; Tomohiro Ojima; Kotaro Yamakado; Tomonari Ando; Shin Watanabe; Seigaku Hayashi; Hiroyuki Tsuchiya (Case Reports in Orthopedics)
Isolated cuboid fractures are very rare, since they typically occur in combination with midfoot fractures or dislocations. A 61-year-old man presented at our hospital with pain and swelling on the outside of his right foot. The lateral column of his right foot was shortened by approximately 6.5 mm on X-ray. CT showed displacement of the joint surface between the cuboid and the fourth metatarsal, with a 3.5 mm depression. An MRI revealed no other injuries. Based on these findings, we diagnosed the patient with an isolated nutcracker fracture of the cuboid. Using a 1.9 mm arthroscope, we examined the Lisfranc joint. Then the depressed fragments were elevated until the regular joint line was restored. A bone biopsy needle was then used to fill in the large defect with artificial bone. In this case, we did not plate the fracture. Six months after surgery, patient could walk without pain. We report a very rare case of isolated nutcracker fracture of the cuboid. In addition, we suggest our new treatment plan of this fracture.